2023
DOI: 10.3390/su15054035
|View full text |Cite
|
Sign up to set email alerts
|

Developing an MCDM Model for the Benefits, Opportunities, Costs and Risks of BIM Adoption

Abstract: Building information modeling (BIM) offers various deterministic and uncertain benefits and costs. Although there are similarities between such costs and benefits in developed and developing countries, these factors should be analyzed carefully for each region/country due to differences in economic and technical status as well as available policies and regulations. Numerous studies have demonstrated the benefits and shortcomings of BIM adoption around the globe; however, there is scarce comprehensive research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…As part of the CBA, all costs and benefits associated with BIM are identified and quantified, including those that are hard to quantify financially, such as improved safety, reduced rework and enhanced collaboration (Love et al, 2013;Zakeri et al, 2023). After comparing the benefits and costs, it is determined whether the investment is economically feasible (S anchez et al, 2022).…”
Section: Quantification Of Building Information Modelling Investment ...mentioning
confidence: 99%
See 3 more Smart Citations
“…As part of the CBA, all costs and benefits associated with BIM are identified and quantified, including those that are hard to quantify financially, such as improved safety, reduced rework and enhanced collaboration (Love et al, 2013;Zakeri et al, 2023). After comparing the benefits and costs, it is determined whether the investment is economically feasible (S anchez et al, 2022).…”
Section: Quantification Of Building Information Modelling Investment ...mentioning
confidence: 99%
“…A typical construction project will involve numerous requests for information (RFIs) that can be time-consuming and expensive (Morales et al, 2022). However, with the use of BIM, the number of RFIs can be greatly reduced (Toan et al, 2022;Zakeri et al, 2023). To prevent errors and omissions that would typically result in RFIs during construction, BIM allows construction professionals to collaborate and identify potential issues before construction begins (Tu et al, 2023).…”
Section: Requests For Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang Wenjing proposed a BIM-based prefabricated building component automation system and concluded that the design results of this system were scientific, effective, and sustainable [8]. Zakeri et al investigated the benefits, opportunities, costs, and risks (BOCR) associated with the implementation of BIM in a developing country while using a new multi-criteria decision-making approach (i.e., fuzzy reduced analytic Hierarchy Process) to analyze BOCR separately, providing practitioners with insights into the adoption of BIM [9]. Ren Xingchen introduced a technical route for the application of prefabricated BIM technology in the whole life cycle stage and concluded that the integrated application of the existing BIM software and self-developed BIM software could optimize the design scheme and construction and facilitate the later operation and maintenance [10].…”
Section: Introductionmentioning
confidence: 99%